THE USE OF THINK-PAIR-SHARE (TPS) TO INCREASE THE ABILITY OF THE FIRST YEAR STUDENTS OF SMAN 1 TEMBILAHAN KOTA IN COMPREHENDING NARRATIVE TEXT - Robi Milano Robi Milano; Erni Erni Erni; Mahdum Mahdum Mahdum (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract - This study aimed to find out whether or not Think-Pair-Share Strategy could increase the ability of the first year students of SMAN 1 Tembilahan Kota in comprehending narrative texts. The subjects were 22 students from class X.1 at SMAN 1 Tembilahan Kota. This study was classroom action research which was divided into two cycles, in which every cycle consisted of four stages which were plan, action, observation, and reflection. The data collection techniques consisted of observation, field note, and tests (pre-test, summative tests, and post-test). Observation sheets and field notes used to gain the record of the classroom activity during doing the treatments. Pre-test was done before action, summative tests were done after treatment given in each meeting, and post-test was done after the second cycle finished. In analyzing the data, the writer used formula by Hatch and Farhady (1982). The findings of this study indicated that TPS Strategy could increase the students ability in which there were 17 students or 77.3% of the students could achieve the standard minimum criteria of achievement (KKM) with average was 74,5. In addition, the percentage of students’ activities was also increased from the first to the last meetings. Moreover, the result of observation sheets and field notes showed a positive behavior in a process of learning and it also helped students to increase their reading ability and more active in learning and it also helped students to increase their reading ability and more active in learning process.   Keywords: Think-Pair-Share, students reading ability, narrative text